Nonoperating room regional anesthesia in pediatric patients: A review of indications and challenges - Vikram Chandra; Amarjeet Kumar; Chandni Sinha; Ajeet Kumar (Wolters Kluwer -Medknow Publications, 2024)
Nonoperating room regional anesthesia (NORRA) involves providing regional anesthesia in environments other than the standard operating rooms, such as in intensive care units, emergency departments, or interventional radiology suites. Although regional anesthesia is well-documented for its benefits in perioperative care, its application in nonoperating room environments remains limited. We conducted a narrative literature review using various databases such as PubMed, Embase, Medline, Ovid, PMC, and Google Scholar. Our search strategy involved using different combinations of terms associated with regional anesthesia, nonoperating room anesthesia, intensive care units, and pediatric patients. Regional anesthesia offers significant benefits for pediatric patients, such as reducing the need for opioids and enhancing autonomic, metabolic, and immunological responses. Techniques used in NORRA include central neuraxial blocks, peripheral nerve blocks, and topical anesthesia, with common anesthetic agents being lidocaine, bupivacaine, and eutectic mixture of local anesthetic cream. This review investigates the applications, indications, challenges, and future prospects of NORRA in pediatric patients.